Functional characterization of poly(N-isopropylacrylamide) nanohydrogels for the controlled release of food preservatives - Fuciños, C. (2014)
In most active packaging systems for food applications, the preservative release is uncontrolled and frequently ineffective due to excessive or insufficient preservative concentration in the food matrix at a particular time. This work was aimed to evaluate the usefulness of pH- and temperature-sensitive poly(N-isopropylacrylamide) nanohydrogels for developing smart delivery systems to release preservatives as a response to environmental triggers. Pimaricin was used as a model preservative. Loading and release efficiencies were studied as a function of incorporation time and nanohydrogels composition, that differed in the cross-linker and acrylic acid content. Pimaricin loading efficiency was not affected by the acrylic acid. However, the cross-linking degree and incorporation time had a great influence. The lower the cross-linker content, the higher the loading efficiency, which in all cases exceeded 70 % at 12 h, approaching 100 % after 60 h of incorporation. No significant differences were observed between loading efficiencies obtained using water or methanol for pimaricin solubilisation. On the other hand, pimaricin release was dependent on the gel collapse, determined by the gel composition. Increasing the cross-linker content enhanced the nanoparticles' rigidity, and inclusion of acrylic acid as comonomer promoted strong electrostatic repulsions among the polymer chains. In both cases, the collapse was hampered, leading to a more hydrated collapsed state that favoured a sustained release of pimaricin. A mathematical model was also developed to predict the pimaricin release as a function of pH, temperature and storage time, allowing to select the most suitable nanohydrogel for a specific food application.